Penanggulangan Kemiskinan: Perspektif Model Koneksi Sosial di Kabupaten Sumbawa - Isnaini Muallidin (Jurnal Bina Praja, 2025)
This study examines poverty alleviation efforts in the Sumbawa Regency through the lens of the Social Connection Model proposed by Iris Marion Young. Despite various government interventions, poverty remains a persistent challenge in this regency. The study investigates how strengthening social connections among stakeholders (government institutions, local communities, the private sector, and civil society organizations) can create more effective poverty reduction strategies. Using a qualitative approach, the study identifies structural barriers to poverty alleviation and explores how collective responsibility and joint action can address these barriers. The findings reveal that poverty in Sumbawa Regency is exacerbated by weak inter-institutional coordination, limited community participation in policy development, and insufficient attention to local contexts and cultural factors. The study demonstrates that applying the principles of the Social Connection Model, such as collective responsibility, forward-looking action, and collaborative governance, can significantly enhance poverty reduction outcomes. This research contributes to the growing literature on participatory approaches to poverty alleviation by offering practical insights for policymakers and development practitioners working in rural Indonesian contexts.